Nutritional analysis of Colocasia esculenta l. tubers aqueous extract and comparative analysis with existing literature (Sciences of Phytochemistry, 2023)
Taro (C. esculenta L.) is a plant in the Araceae family that is farmed as a tuber. This plant is one of the non-animal sources of nutrients, minerals, and trace elements and has had numerous biological activities. Taro plants offer antidiabetic, antibacterial, antifungal, antioxidant, and antihepatotoxic properties. To have better nutritional content and wider and longer-lasting applications in culinary products, the taro tuber requires going through a process that increases its use value, one of which is extraction. The research aim of this work was to use several analytical methods to determine the nutrition components in the aqueous extract of C. esculenta L. Some of the nutrients found in the aqueous extract of C. esculenta L. consist of total protein 10.9%, total carbohydrate 75.5%, amylose 8.20%, amylopectin 43.6%, starch 51.8%, omega 6 0.2%, and fat-soluble vitamins A, D, and E at 0.5 IU/100gr, 24.8 g/100gr, and 0.01 mg/100 gr. Water-soluble vitamins B1, B2, B6, and C were present in amounts of 4.55, 1.96, 0.17, and 0.70 mg/kg, respectively. C. esculenta L. aqueous extract also included minerals such as the trace elements sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), and zinc (Zn) in the amounts of 35.2, 4638, 137, 129, 47.9, and 13.8 (mg/100gram), respectively. The aqueous extract of C. esculenta L. tubers includes a variety of nutrients and offers the potential to be consumed as a functional food.